Abusing Youth Theologically Understanding Youth Through Misunderstanding Disability - Langford, Michael D. (2018)
Young people and folks who are disabled have a lot in common. Often, both groups are considered to lack certain characteristics that would qualify them as being "normal," as defined by a culturo-scientific anthropology. However, this delimitation, which leads to abusive exclusion and marginalization, might find theological healing. This article first examines the problematic definition of "disability," and how theology at times has been used to buttress that definition. In response, a theological anthropology is then suggested that allows for difference of ability, leading to a theological model of disability. Finally, in light of the commonality between disability and youth, this same theological anthropology offers a theological model of youth that allows for the affirmation of young people's full humanity and belonging.
Keywords: Theological Anthropology; Disability Studies; Practical Theology; Systematic Theology; Youth Ministry